From life cycle assessment to grass‐based agriculture: A review and application - Yutong Li; Shu Jin; Xiaoping Xin; Yi An; Lili Huo; Changliang Shao; Lulu Wang; Xiaoyu Zhu (Grassland Research, 2025)
Abstract Life cycle assessment (LCA) serves as an essential tool for the quantitative evaluation of production efficiency, environmental impacts, and sustainability across the entire life cycle of grass‐based agricultural systems. This study systematically examines the progress of LCA applications in grass‐based agriculture, analyzes the shortcomings of current methods, and proposes a new LCA approach based on an economic, social, and environmental multidimensional framework. The study emphasizes (1) the selection of LCA methods should align with specific research objectives, focusing not only on environmental impacts but also comprehensively considering social impacts and economic benefits; (2) it provides a comprehensive overview with an expanded scope selection beyond the “from cradle to farm gate” boundary and uses product value as the functional unit to facilitate assessments across various crop types, particularly focusing on inventory analysis and impact assessment; (3) challenges including model integration, impact sensitivity, and data uncertainty persist in the LCA of grass‐based agriculture; and (4) multidimensional frameworks effectively integrate both quantitative and qualitative factors into grass‐based agriculture, further enhancing the understanding of LCA results and supporting decision‐making. Addressing these challenges through the integration of LCA with other models facilitates the sustainable evolution of grass‐based agriculture, ensuring its long‐term viability.